Determinants and definition of abdominal obesity as related to risk of diabetes, metabolic syndrome and coronary disease in Turkish men:: A prospective cohort study - Onat, Altan; Uyarel, Huseyin; Hergenc, Gulay; Karabulut, Ahmet; Albayrak, Sinan; Can, Gunay (ELSEVIER IRELAND LTD, 2007)
We aimed to investigate determinants of abdominal obesity and its clinical impact on metabolic syndrome (MS), diabetes (DM) and coronary heart disease (CHD) in men. Methods: Prospective evaluation of 1638 male participants (aged 48.5 +/- 12.3), representative of Turkey's men who have a high prevalence of MS. For components of MS, criteria of NCEP guidelines were adopted, modified for abdominal obesity. Follow-up constituted 9650 person-years. Results: Insulin level (relative risk [RR] 1.40 for doubling), C-reactive protein (CRP) and heavy smoking (protective) were independent predictors of newly developing abdominal obesity. High triglyceride and low HDL-cholesterol were significantly associated already with waist girth quartile II, apolipoprotein B with quartile III. Waist girth significantly predicted future MS from quartile II on, independent of insulin resistance (IR) by homeostatic model assessment, whereby its hazard ratio (HR, 2.6) exceeded double that of HOMA. CRP independently predicted MS. Age-adjusted HR of waist girth (1.59) was significant in predicting DM. Age- and smoking-adjusted top waist quartile conferred significant risk for incident CHD (RR 1.71) but not for overall mortality. As judged by sensitivity and specificity rates for future CHD, DM and MS, abdominal obesity was most appropriately defined with a waist girth of >= 95 cm, and an action level 1 of >= 87 cm was proposed for MS in this population. Conclusions: Serum insulin, CRP levels and (inversely) heavy smoking are predictors for abdominal obesity in Turkish men. Atherogenic dyslipidemia and elevated blood pressure are associated significantly already with modest rises in waist girth adjusted for age and smoking. Abdominal obesity shows substantial independence of IR in the development of MS. Increasing waist girth was predictive of MS, more strongly than of DM. Risk for CHD imparted by abdominal obesity is essentially mediated by risk factors it induces. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: abdominal obesity; coronary heart disease; diabetes mellitus; hypertension; metabolic syndrome; proinflammatory state; cigarette smoking; C-REACTIVE PROTEIN; INSULIN-RESISTANCE; HEART-DISEASE; CARDIOVASCULAR RISK; VISCERAL ADIPOSITY; POPULATION; ASSOCIATION; FEATURES; GLUCOSE; Cardiovascular System & Cardiology